New Organic Dyes Based on Biarylmethylene‐Bridged Triphenylamine for Dye Sensitized Solar Cell. Issue 8 (5th May 2015) - Wu, Fei; Liu, Haitao; Lee, Lawrence Tien Lin; Chen, Tao; Wang, Min; Zhu, Linna
Abstract Three new organic dyes were synthesized and characterized for applications in dye‐sensitized solar cells (DSSCs). In these dyes, diarylmethylene‐bridged triphenylamine is the donor, and different acceptors and vinylthiophene are designed to get TBA‐1, TBA‐2 and TBA‐3. Their photophysical, electrochemical and photovoltaic properties were investigated, and the effects of the acceptor structures as well as the linkage on these properties were evaluated. Results demonstrated that the vinylthiophene linkage between the donor and the acceptor is favorable for improving light harvesting ability of TBA‐2. In addition, the electrochemical impedance spectroscopy experiments suggest larger Rrec and longer electron lifetime of TBA‐2. Therefore, it outperforms the other dyes, exhibiting the highest power conversion efficiency of 3.87%, with Jsc of 8.25 mA·cm−2 and Voc of 666 mV. Unfortunately, the TBA‐3 with three acceptor groups only shows efficiency of 3.52%, indicating that the design of increasing acceptor groups plays little role on enhancing the solar cell efficiency.